The Effect of Capital Adequacy Ratio, Return on Asset, Loan to Deposit Ratio and Non Performing Loan on Stock Prices of Banking Companies Listed on the Indonesia Stock Exchange in the 2022 Period - Rafika Febriana Dwi Lestari; Arik Susbiyani; Riyanto Setiawan Suharsono (Westscience Press, 2024)
This study aims to determine the effect of Capital Adequacy Ratio, Return On Assets, Loan To Deposit Ratio and Non Performing Loan on Stock Prices in Companies listed on the IDX for the 2022 Period. The research method used is a descriptive method with a quantitative approach. The population in this study is the financial statements of Conventional Banking. The data method used in this study is multiple linear regression analysis, classical assumption tests including normality tests, multicollinearity tests, heteroscedasticity tests. Significance tests include t-tests, as well as correlation coefficients and determination coefficients at a significance level of 5%. Data are processed and analyzed using the SPSS version 27 application program. The results of this study indicate that partially the Capital Adequacy Ratio has a significant negative effect on stock prices, with a Tcount value of -2.875 <0.05. Partially, Return On Assets has a significant positive effect on Stock Price, with a calculated T value (7.515) >< Ttable 2.034 with a significance value of 0.000 < 0.05. Partially, Loan to Deposit Ratio has a significant negative effect on stock price, with a calculated T value (- 3.684) < Ttable 2.034 with a significance value of 0.001 < 0.05. Partially, Non Performing Loan has a significant negative effect on Stock Price, with a calculated T value (-2.991) < Ttable 2.034 with a significance value of 0.005 < 0.05.